Gene therapy for diabetic foot ulcers: Interim analysis of a randomised, placebo‐controlled phase 3 study of VM202 (ENGENSIS), a plasmid DNA expressing two isoforms of human hepatocyte growth factor - Perin, Emerson; Loveland, Lacey; Caporusso, Joseph; Dove, Cyaandi; Motley, Travis; Sigal, Felix; Vartivarian, Mher; Oliva, Francisco; Armstrong, David G (International wound journal, 2023)
To evaluate the status of a 7‐month phase 3 study conducted to test the effect of intramuscular injections of VM202 (ENGENSIS), a plasmid DNA encoding human hepatocyte growth factor, into the calf muscles of chronic nonhealing diabetic foot ulcers with concomitant peripheral artery disease. The phase 3 study, originally aimed to recruit 300 subjects, was discontinued because of slow patient recruitment. An unprespecified interim analysis was performed for the 44 subjects enrolled to assess the status and determine the future direction. Statistical analyses were carried out for the Intent‐to‐Treat (ITT) population and separately for subjects with neuroischemic ulcers, using a t‐test and Fisher's exact test. A logistic regression analysis was also conducted. VM202 was safe and potentially should have benefits. In the ITT population (N = 44), there was a positive trend toward closure in the VM202 group from 3 to 6 months but with no statistical significance. Levels of ulcer volume or area were found to be highly skewed between the placebo and VM202 groups. Forty subjects, excluding four outliers in both arms, showed significant wound‐closing effects at month 6 (P = .0457). In 23 patients with neuroischemic ulcers, the percentage of subjects reaching complete ulcer closure was significantly higher in the VM202 group at months 3, 4, and 5 (P = .0391, .0391, and .0361). When two outliers were excluded, a significant difference was evident in months 3, 4, 5, and 6 (P = .03 for all points). A potentially clinically meaningful 0.15 increase in Ankle‐Brachial Index was observed in the VM202 group at day 210 in the ITT population (P = .0776). Intramuscular injections of VM202 plasmid DNA to calf muscle may have promise in the treatment of chronic neuroischemic diabetic foot ulcers (DFUs). Given the safety profile and potential healing effects, continuing a larger DFU study is warranted with modifications of the current protocol and expansion of enrolling sites.